Lipid Profile and Atherogenic Index of Plasma (AIP) in Vegetarians (Journal of Enam Medical College, 2015)
Background: Diet deficient in fresh fruits and vegetables are associated with an increased risk of coronary diseases. Low levels of vitamin C, vitamin E and other antioxidants may enhance the production of oxidized LDL and are important independent risk factors for coronary disease. Objective: To make a comparative evaluation of lipid profile and atherogenic index of plasma (AIP) between vegetarians and nonvegetarians. Materials and Methods: This case-control study was carried out in the Department of Biochemistry of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between July 2011 to June 2012. Vegetarian and nonvegetarian subjects of male sex were the study population. Vegetarians were considered as cases while nonvegetarians as controls. After proper ethical consideration a total of 30 vegetarians and 40 nonvegetarians were consecutively included in the study based on predefined inclusion and exclusion criteria. Laboratory investigations were done in the Department of Biochemistry, BSMMU, Dhaka. Results: The vegetarians had significantly lower total cholesterol and LDLcholesterol than the nonvegetarians (p=0.000 and p=0.000 respectively). Serum HDL cholesterol was also lower among the vegetarians (p=0.002) and triglycerides were almost identical in both the groups (p=0.272). Conclusion: The study reveals lower level of total cholesterol, LDLcholesterol and HDL-cholesterol in vegetarians. No difference regarding triglycerides and AIP was found between the groups. So, the findings of this study do not indicate any superiority of vegetarian diet in control and prevention of cardiac diseases. DOI: http://dx.doi.org/10.3329/jemc.v5i1.21494 J Enam Med Col 2015; 5(1): 30-33